The private sector on the peacebuilding in Colombian postconflict: A theoretical study (2020)
With the signing of the Peace Agreement between the national government of Colombia and the then Revolutionary Armed Forces of Colombia - Ejército del Pueblo (FARC-EP) in 2016, a post-conflict scenario begins in Colombia, characterized by a series of challenges and the need for input from various actors, including the business sector. The objective of this article is to explore and analyze the practices and actions that companies can carry out to contribute to the construction of peace. To this end, an exploratory research was carried out with a documentary design divided into two phases, on the one hand, a review of the literature on peacebuilding business practices, and on the other, a documentary analysis on guides and peacebuilding proposals from national and international organizations. The results suggest that the companies support the construction of peace mainly from CSR practices and shared value oriented to economic development. This corresponds to the guidelines of national and international organizations that are geared towards generating jobs and entrepreneurship projects.